Activation characteristics of the primary motor (M1) and supplementary motor (SMA) areas during robust unilateral finger tapping task - Ahmad Nazlim Yusoff; Mazlyfarina Mohamad; Khairiah Abdul Hamid; Aini Ismafairus Abd Hamid; Hanani Abdul Manan; Mohd Harith Hashim (Penerbit UKM, 2010)
This study investigated the functional specialisation characteristics of brain in multiple right-hand dominant subjects pertaining to the activation of the cerebral motor cortices evoked by unilateral finger tapping, especially in primary motor (M1) and supplementary motor (SMA) areas. This multiple-subject study used unilateral (UNIright and UNIleft) selfpaced tapping of hand fingers to activate the M1 and SMA. Brain activation characteristics were analysed using statistical parametric mapping (SPM). Activation for UNIright and UNIleft showed the involvement of contralateral and ipsilateral M1 and SMA. A larger activation area but with a lower percentage of signal change (PSC) were observed in the left M1 due to the control on UNIright (4164 voxels at α = 0.001, PSC = 1.650) as compared to the right M1 due to the control on UNIleft (2012 voxels at α = 0.001, PSC = 2.377). This is due to the influence of the tapping rate effects which is greater than what could be produced by the average effects of the dominant and sub-dominant hands. The significantly higher PSC value observed in the right M1 (p < 0.05) is due to a higher control demand used by the brain in coordinating the tapping of the sub-dominant fingers. The findings obtained from this study showed strong evidence of the existence of brain functional specialisation and could be used as baseline references in determining the most probable motor pathways in a sample of subjects.